The Effect of Multimedia-Based Education on Knowledge, Attitudes, and Behavior Hypertension Patients in Stroke Prevention - Manurung, Santa; Suratun, Suratun; Wartonah, Wartonah; Ekarini, Ni Luh Putu; Maryam, Raden Siti (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
The prevalence of hypertension continues to increase, and various epidemiological studies revealed an increase in the incidence of hypertension in different parts of the world. According to the American Heart Association (AHA), The number of Americans over the age of 20 who suffer from hypertension has risen to 74.5 million, while nearly 90% of cases have no identified cause. If not treated effectively, hypertension may cause damage to blood vessels throughout the body, the most prominent of which is the danger of damage to the brain, eyes, heart, and kidneys. An introduction to stroke is essential for reducing the risk of stroke in people with hypertension. Multimedia is one of the developments in health education media, which is in accordance with the advancement of digital technology, incorporating stroke prevention. This study aims to examine the impact of multimedia-based education on hypertension patients' knowledge, attitudes, and behavior toward stroke prevention. This research is a quasi-experiment with a pre-posttest with a control group design. The sampling technique employed was simple random sampling, and the sample size determination utilized a hypothesis test of the average difference in two independent groups of 60 respondents. Data analysis in this study administered paired t-test and independent t-test. The results unveiled that there were significant differences in knowledge (p=0.022), attitudes (p=0.001), and behavior (p=0.008) of hypertension patients in preventing stroke after intervention in the form of multimedia-based education. Therefore, it is recommended that the community can perform hypertension treatment independently frequently, and the implementation of the prolanis program can be enhanced so that people can receive services easily and regularly to prevent stroke.